Evaluate: an evaluation instrument for measuring students' perceptions of their engagement and learning outcomes - Oliver, Beverley; Tucker, Beatrice; Gupta, Ritu; Yeo, Shelley (Routeledge, Taylor & Francis Group, 2008)
In the current climate in Australian higher education, quality assurance in university teachingis a priority. In particular, the introduction of the Learning and Teaching Performance Fund (LTPF) has refocused attention on universities? internal student evaluation survey instruments.This paper reports the development, validation and implementation of a new unit surveyinstrument which prompts students to reflect on what helps their achievement of unit learningoutcomes, and to report their levels of motivation, engagement and overall satisfaction with asemester-long course or unit of study. The instrument (eVALUate) was created from preceptsreported in the research literature, current practices in evaluating teaching, and sound qualityassurance practices appropriate to a university outcomes-focused education paradigm.